Analisis Dakwah Digital Felix Siauw Sebagai Pendakwah dan Influencer - Dzaki Anshari, Muhammad; Nirwan Syafrin; Rosmawati (Universitas Ibn Khaldun Bogor, 2025)
Da'wah as a public speaking activity always requires digitalization. Today's developments which lead society to grow together with advances in technology and information require massive digitalization of information in an effort to convey messages well. Digitizing da'wah messages is one form of effort to maintain da'wah in people's lives, especially in the digital era. Felix Siauw, as a well-known digital preacher with 5.3 million followers on his Instagram social media account, is able to influence society regarding the idea of